2001
DOI: 10.1007/s004280100425
|View full text |Cite
|
Sign up to set email alerts
|

Cytological characterization of apatitic calcium phosphate structures in bronchial epithelial tissue cultured from a child with cystic fibrosis (ΔF508)

Abstract: Patients with cystic fibrosis homozygous for the AF508 mutation have marked disturbances in ion exchanges in a variety of tissues. Alterations in intra- or extracellular levels of Ca2+ and calcifications have been observed in numerous tissues from such patients, although the nature and origin of such calcifications have yet to be elucidated. In this study, we investigated the formation of calcifications in the respiratory tract of a AF508 homozygous child and attempted to establish their origin. Samples of bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…They were found as clusters of needle-like crystals surrounded by amorphous material. EDX and electronic diffraction analysis showed that they were Ca-P crystals close to apatite composition (Table 5), which have already been described generally in pathological cases of animal tissues (Hering et al, 1987;Hollande et al, 1990;Cantet et al, 2001). To our knowledge, calcium phosphate crystals have not yet been described in plants.…”
Section: Damages On V Faba L As a Response To Metal Contamination: mentioning
confidence: 52%
“…They were found as clusters of needle-like crystals surrounded by amorphous material. EDX and electronic diffraction analysis showed that they were Ca-P crystals close to apatite composition (Table 5), which have already been described generally in pathological cases of animal tissues (Hering et al, 1987;Hollande et al, 1990;Cantet et al, 2001). To our knowledge, calcium phosphate crystals have not yet been described in plants.…”
Section: Damages On V Faba L As a Response To Metal Contamination: mentioning
confidence: 52%
“…On the other hand, the low crystallinity may also correspond to the presence of carbonate substitutions in the crystal lattice [49]. Diffraction patterns with similar fuzzy concentric rings were also observed in dentin [64] and calcified cartilage [65], as well as in tissues undergoing extraskeletal calcification [66], which were also interpreted as the presence of HAP possessing a low degree of crystallinity. As a further reference, diffraction patterns of the mineral precursor in bones produced amorphous diffraction patterns while more mature bone harbored both fuzzy rings and dots similar to the more crystalline patterns obtained for some of our serum granulations [67].…”
Section: Resultsmentioning
confidence: 79%
“…The authors hypothesized that the calcium was possibly sequestered by mitochondria and Golgi apparatus partly due to an increase in electron transport chain activity. 7 We believe the parenchymal calcifications found in this case signify ongoing chronic inflammation consistent with the dystrophic type of lung calcifications. The lack of causative organism or hamartoma raises the question if this is an inherent property of CF.…”
Section: Discussionmentioning
confidence: 56%
“…Extensive parenchymal calcification as in our child has never been previously reported. Cantet and colleagues 7 reported seeing crystalline structures on cytological analysis of lung tissue from a patient with CF following lobectomy which were likely to be calcium phosphate deposits. 7 It is unclear if the calcification was seen macroscopically in that case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation